1983
DOI: 10.1095/biolreprod28.5.1114
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins in Swine Blastocysts

Abstract: The activity of phospholipase A2 (PLA2) and the content of prostaglandins (PGF and PGE-A) in swine blastocysts were determined on Days 7 through 14 of gestation by using radioenzymatic and radioimmunoassay techniques. Both PLA2 activity and PG content increased in the blastocyst with age. PLA2 activity on Day 14 and PG content on Day 12 were significantly higher than those on earlier stages of pregnancy. The content of PGE-A was always greater than that of PGF and the difference became significant on Days 11 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 23 publications
5
24
0
Order By: Relevance
“…Analogous to other systems, these findings suggested that the zebrafish Ptges functions downstream of COX-1 during gastrulation to generate PGE 2 . Accordingly measurements of prostaglandin levels using mass spectrometry revealed the production of PGE 2 during gastrulation, along with PGF 2␣ (prostaglandin F 2␣ ) and PGI 2 (Cha et al 2005a), which parallels studies demonstrating the presence of PGE 2 and PGF 2␣ in developing mammalian blastocysts (Davis et al 1983).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Analogous to other systems, these findings suggested that the zebrafish Ptges functions downstream of COX-1 during gastrulation to generate PGE 2 . Accordingly measurements of prostaglandin levels using mass spectrometry revealed the production of PGE 2 during gastrulation, along with PGF 2␣ (prostaglandin F 2␣ ) and PGI 2 (Cha et al 2005a), which parallels studies demonstrating the presence of PGE 2 and PGF 2␣ in developing mammalian blastocysts (Davis et al 1983).…”
Section: Resultssupporting
confidence: 70%
“…Given the vital role of prostaglandins in normal physiologic settings, it has been hypothesized that the maternal contribution of prostaglandins in the placenta allows the prostaglandindeficient embryos to develop normally (Reese et al 2000(Reese et al , 2001. Consistent with this notion, mammalian blastocysts produce high levels of PGE 2 and PGF 2␣ (Dey et al 1980;Davis et al 1983), and murine blastocysts cultured outside of the uterus do not survive in the presence of COX inhibitors (H. Wang and S.K. Dey, pers.…”
Section: Discussionmentioning
confidence: 98%
“…IL1B can also stimulate phospholipase A2 (PLA2) (Kol et al 2002 ) which increases membrane fl uidity through the release of arachidonic acid from the phospholipid bilayer of the cell membrane. The increase of plasminogen activator and PLA2 activity during elongation of the conceptus (Davis et al 1983 ) would be consistent with a role for IL1B2 in the induction of rapid cellular remodeling. The release of arachidonic acid from the conceptus trophoblast contributes to increases in secretion of PGs from the conceptus during and following elongation as conceptus expression of PTGS2 also increases (Wilson et al 2002 ).…”
Section: Expression Of Interleukin 1 Beta (Il1b) By Conceptusessupporting
confidence: 56%
“…Changes in levels of certain hormones, proteins and minerals in histotroph before day 12 of pregnancy (Geisert et al 1982a;Zavy et al 1984; will, therefore, be independent of changes in maternal endocrine function, suggesting that preimplantation embryos have a capacity to modify their own microenvironment before the maternal recognition of pregnancy. In this respect, hormones secreted by blastocysts could induce local changes in endometrial activity which are consistent with changes in the composition of histotroph during the first 10 days of pregnancy (Knight et al 1973;Basha et al 1980;Adams et al 1981;Geisert et al 1982a) and several groups have now reported capacities for steroid Heap et al 1981) and PG (Watson and Patek 1979;Davis et al 1983) synthesis by dispersed tissues of pig blastocysts collected after day 10 of gestation. Specific inhibition of endocrine activities of blastocysts is associated with impaired implantation, degenerative changes and early intrauterine mortality EI-Banna et al 1970;Hoffman 1978;Hurst and MacFarlane 1981).…”
Section: Introductionmentioning
confidence: 57%